Fabrication & characterization of biomaterials from hydroxylethyl cellulose sponges coated with hydroxy apatite - Hassanal, Haris (2019)
Hydroxyapatite composites have been recognized as' substitute materials for bone and teeth in orthopedic and dentistry field due to their chemical and biological similarity to human hard tissue. This biocompatible and bioactive material can be used to restore damaged human calcified tissue. Porous hydroxyapatite exhibits strong bonding to the bone, the pores provide a mechanical interlock leading to a firm fixation of the material. Porous hydroxyapatite is more resorbable and more osteoconductive than its dense counterpart and in porous form the surface area is greatly increased which allows more cells to be carried in comparison with dense hydroxyapatite. Most methods in producing HA used chemicals and some of them are very harmful to human being. This thesis is focused on the crystallization and characterization of hydroxyapatite (HA), on porous hydroxyethyl cellulose (HEC) which is a water-soluble, biocompatible and biodegradable polymer. Porous HEC sponges were prepared by freeze-drying method. Hydroxyethyl cellulose (HEC) is a gel like substance and is widely used in industries. The crystallization of hydroxyapatite (HA) was done by immersing HEC sponges into various concentration of simulated body fluid (SBF) for different time periods. For the analysis of these materials various bulk and particle level characterization techniques have been employed, which includes Scanning Electron Microscope (SEM), Fourier transform infrared spectroscopy (FTIR), Thermogravimetry (TGA), and mechanical testing. FTIR analysis were used to confirm the deposition of apatite on the surface of HEC sponges. HEC with different concentration like 1 wt%, 3 wt%, 5 wt%, were used to form the sponges and they were coated with the· HA, and these acted as scaffolds. It was found that porosity, pore size and pore inter connectivity depends upon the concentration of the HEC. The size of the HA crystals increased with the concentration of the HEC. The sponges had pores with diameter-2-60µm and pores were interconnected. In-vitro testing with human dental pulps stem cell (DPSC) was also conducted to assess its biocompatibility. In-vitro bioactivity and biodegradability studies show that the HECIHA scaffold was bioactive as well as bioresorbable. The hydroxyethyl cellulose-hydroxyapatite composite is synthesized by incubation in aqueous salt solutions at physiological pH and ambient temperature. Combining hydroxyapatite into hydroxyethyl cellulose may generate a composite with favorable mechanical and chemical properties that are appropriate for various medical applications.